Vaginal delivery in SARS‐CoV‐2‐infected pregnant women in Northern Italy: a retrospective analysis. (28th May 2020) - Ferrazzi, E; Frigerio, L; Savasi, V; Vergani, P; Prefumo, F; Barresi, S; Bianchi, S; Ciriello, E; Facchinetti, F; Gervasi, MT; Iurlaro, E; Kustermann, A; et al.
Abstract : Objective: To report mode of delivery and immediate neonatal outcome in women infected with COVID‐19. Design: Retrospective study. Setting: Twelve hospitals in northern Italy. Participants: Pregnant women with COVID‐19‐confirmed infection who delivered. Exposure: COVID 19 infection in pregnancy. Methods: SARS‐CoV‐2‐infected women who were admitted and delivered from 1 to 20 March 2020 were eligible. Data were collected from the clinical records using a standardised questionnaire on maternal general characteristics, any medical or obstetric co‐morbidity, course of pregnancy, clinical signs and symptoms, treatment of COVID 19 infection, mode of delivery, neonatal data and breastfeeding. Main outcome and measures: Data on mode of delivery and neonatal outcome. Results: In all, 42 women with COVID‐19 delivered at the participating centres; 24 (57.1%, 95% CI 41.0–72.3) delivered vaginally. An elective caesarean section was performed in 18/42 (42.9%, 95% CI 27.7–59.0) cases: in eight cases the indication was unrelated to COVID‐19 infection. Pneumonia was diagnosed in 19/42 (45.2%, 95% CI 29.8–61.3) cases: of these, 7/19 (36.8%, 95% CI 16.3–61.6) required oxygen support and 4/19 (21.1%, 95% CI 6.1–45.6) were admitted to a critical care unit. Two women with COVID‐19 breastfed without a mask because infection was diagnosed in the postpartum period: their newborns tested positive for SARS‐Cov‐2 infection. In one case, a newborn had a positive test after a vaginal operative delivery. Conclusions: Although postpartum infection cannot be excluded with 100% certainty, these findings suggest that vaginal delivery is associated with a low risk of intrapartum SARS‐Cov‐2 transmission to the newborn. Tweetable abstract: This study suggests that vaginal delivery may be associated with a low risk of intrapartum SARS‐Cov‐2 transmission to the newborn. Tweetable abstract: This study suggests that vaginal delivery may be associated with a low risk of intrapartum SARS‐Cov‐2 transmission to the newborn. This article includes Author Insights, a video abstract available at https://vimeo.com/rcog/authorinsights16278